The Emotional and Social Challenges of Child Labourers in Nigeria - Omorogiuwa, Tracy B.E. (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
Child labour has several negative effects, some of which include harm to the children's social and emotional development. In the Benin metropolis of Egor and Oredo Local Government Areas in Edo State, Nigeria, eight working children between the ages of seven and fourteen will have their psychosocial effects from the child labour problem examined in this study. The research's theoretical model was informed by the ecological theory. Using a narrative method, this qualitative study aims to provide a deeper understanding of children's experiences based on the impact of workload on their development. Through the use of thematic data analysis, it was discovered that children's involvement in wage earning had a detrimental effect on their social and emotional development because of labour. Keywords: Child labour, emotional, social, psychosocial, social work